Reportorial or Essayistic Paradigm? – a Few Remarks about the Sports Report - Siekiera, Rafał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article attempts to decide whether the sports report is more about the information or the commentary. On the basis of an analysis of press material, the author examines different characteristics of the genre and tries to determine their compatibility with the news canon. As the analysis shows, the contemporary sports report is less about news and more about commentary, interpretation and evaluation. Journalists tend to summarize the competition and briefly describe the course of events. It makes the sports report similar to press comment and review.